Diffuse parenchymal neurocysticercosis (Health Renaissance, 2017)
Neurocysticercosis is the commonest parasitic manifestation of brain and the leading cause of seizure in the developing world. It is caused by the ingestion of Taenia solium eggs through contaminated food and especially pork meat. Computed tomography and magnetic resonance imaging are the modality of choice for diagnosis of neurocysticercosis. We report a case of 65 years old male presented with complaint of seizure, which was diagnosed as diffuse parenchymal neurocysticercosis on computed tomography scan of brain. Health Renaissance 2015;13(3): 177-180